Public Health Leadership and Management : Cases and Context. - Capper, Dr. Stuart A. A. (SAGE Publications, 2001)
The six chapters and fifteen cases contained in this book challenge students to ask the appropriate questions and stimulate their thinking about public health leadership and management. The situations presented by each case are vivid and provide not only a basis for practicing professional public health judgements but also provide a lasting impression that aids in retention of the lessons learned.